Un modèle-outil pour fonder l’évaluation en pédagogie active : impact d’une formation sur le développement professionnel des enseignants - Sylviane Bachy; Marcel Lebrun; Denis Smidts (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
A team of academic developers was confronted with the task of organising a three day training course for higher education teachers on the topic of assessment in contexts using active pedagogy.The aim of this paper is to present the various steps in implementing the course, using a framework devised for this course. The course was carried out with 59 teachers in higher education. We will show how using the framework supported instructional design and professional development of teachers.